2021
DOI: 10.3390/vaccines9111253
|View full text |Cite
|
Sign up to set email alerts
|

Immersion Vaccination by a Biomimetic-Mucoadhesive Nanovaccine Induces Humoral Immune Response of Red Tilapia (Oreochromis sp.) against Flavobacterium columnare Challenge

Abstract: Immersion vaccination with a biomimetic mucoadhesive nanovaccine has been shown to induce a strong mucosal immune response against columnaris disease, a serious bacterial disease in farmed red tilapia caused by Flavobacterium columnare. However, the induction of a systemic immune response by the vaccine is yet to be investigated. Here, we examine if a specific humoral immune response is stimulated in tilapia by a biomimetic-mucoadhesive nanovaccine against Flavobacterium columnare using an indirect-enzyme-link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 47 publications
(71 reference statements)
0
16
0
Order By: Relevance
“…There was also evidence that these nanoparticles induced changes in the mucosal‐associated lymphoid tissue. In a more recent study, a significant up‐regulation of igm and igt transcripts was observed in the spleen and kidney of red tilapia vaccinated with the chitosan complex nanoemulsion when infected with F. columnare , demonstrating that the chitosan‐based mucoadhesive vaccine could generate a humoral systemic immune response against columnaris disease in fish vaccinated by immersion 81,82 . Studies have also shown the prophylactic efficacy of nanovaccines against fish viral diseases.…”
Section: Advancements In Nanoparticle Technologies For Tilapia Vaccinesmentioning
confidence: 94%
See 2 more Smart Citations
“…There was also evidence that these nanoparticles induced changes in the mucosal‐associated lymphoid tissue. In a more recent study, a significant up‐regulation of igm and igt transcripts was observed in the spleen and kidney of red tilapia vaccinated with the chitosan complex nanoemulsion when infected with F. columnare , demonstrating that the chitosan‐based mucoadhesive vaccine could generate a humoral systemic immune response against columnaris disease in fish vaccinated by immersion 81,82 . Studies have also shown the prophylactic efficacy of nanovaccines against fish viral diseases.…”
Section: Advancements In Nanoparticle Technologies For Tilapia Vaccinesmentioning
confidence: 94%
“…Some other examples of nanoparticles used to delivery vaccines in aquaculture include the studies by Kitiyodom et al, 69,81,82 who examined the efficacy of chitosan-coated mucoadhesive nanovaccine against columnaris disease delivered to farmed red tilapia by immersion vaccination. This disease is caused by Flavobacterium columnare.…”
Section: Advancements In Nanoparticle Technologies For Tilapia Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Gram-negative motile aeromonads may be treated with potassium permanganate (KMnO 4 ) and with antibiotics in the feed (Monir et al 2020;Prabu et al 2019;Stratev and Odeyemi 2017). A recent study reported immersion vaccination against columnaris disease induced a strong immune response and improved survival against experimental infection of F. columnare (Kitiyodom et al 2021). This opportunistic pathogen, in addition to fungal diseases such as white spots, can also be effectively treated via exposure to CuSO 4 , KMnO 4 , or salt/sodium chloride (El-Sayed 2020;Prabu et al 2019).…”
Section: Diseases and Their Treatments In Tilapia Farmingmentioning
confidence: 99%
“…94,96,100 The mucosal-associated lymphoid tissues (MALTs) are important in preventing pathogen invasion into the fish during the early stages of infection and are associated with skin (skin-associated lymphoid tissue [SALT]), gut (gut-associated lymphoid tissue [GALT]), gills (gill associated lymphoid tissues [GIALT]) and nares (nasopharynxassociated lymphoid tissue [NALT]). 55,101 While the contribution of MALTs in tilapia immunity has not yet been fully elucidated, mucosal vaccination of tilapia with a nanoparticle vaccine against F. columnare, delivered by immersion, was shown to trigger upregulation of IgT, IgM, TNF α, IL1-β and MHC-1 in the gills (mucosal response) 102 and of IgT, IgM, TNF α and IL1-β in the blood (systemic response) 103 of vaccinated fish.…”
Section: Immune System In Tilapiamentioning
confidence: 99%